An Eco-translatology approach to investigating the translation of comics: Case study of The Sayings of Zhuangzi - Chen, Yi-Chiao (Meta, 2023)
Featuring the interplay of verbal and visual content, the translation of comics has received theorists’ attention in recent decades. To shed new light, this study analysed the translation of comics from a new perspective, namely Eco-translatology. Selecting 自然的簫聲：莊子說 [The Sayings of Zhuangzi: The Music of Nature] and its English translation, The Sayings of Zhuangzi: The Music of Nature, as the research texts, this study conducted an in-depth analysis and obtained three major findings: (1) the translators have professional knowledge and expertise to process the comic book appropriately, (2) the target ecosystem shares a similar composition and creates the same effect as the source at the micro- and meso-levels and (3) the target ecosystem is constructed in a composition that attains harmony and interaction at the macro-level. Amplification, reduction/omission and literal translation are the three most-adopted coping strategies to achieve linguistic and cultural transformation, whereas the inclusion of an introduction and the use of footnotes fulfill communicative transformation. This paper argues that translators attach the utmost importance to the “comprehension of stories,” followed by “space constraints,” “fluency of translation,” and “faithfulness to the original meaning.”